Dampak Pola Asuh Orang Tua terhadap Pembentukan Perilaku Remaja - Anjani Lidya Cahaya; Alfani Dwi Putri; Reksa Alvira; Sri Mulyani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study was conducted to understand how parenting styles significantly influence the process of shaping children’s behavior. The method used in this research was a qualitative approach, with data collection carried out through interviews and direct observation of participants aged 10–18 years who live in Cicendo District, Bandung. Based on the results conveyed by several participants, it can be seen that parenting styles play a very important role in children’s growth and development as well as in the formation of their emotional conditions. Parents who play a positive role such as giving more attention, communicating well, and providing full support tend to build positive responses and emotional stability in children. This helps shape a healthy personality and creates a comfortable home environment that makes children feel safe. In contrast, parents who display negative roles and parenting styles such as being harsh, lacking attention, and frequently engaging in conflict tend to make children feel pressured and lack self confidence due to unmet emotional support. As a result, children may limit their relationship with their parents, which leads to emotional instability. Overall, the discussion shows that the family is the primary foundation for children, as their growth and development are strongly influenced by how parents fulfill their roles in shaping children’s personalities, which ultimately impacts their lives in the future.